The holographic universe - Talbot, Michael (HarperCollins Publishers, 1991)
'There is evidence to suggest that our world and everything in it - from snowflakes to maple trees to falling stars and spinning electrons - are only ghostly images, projections from a level of reality literally beyond both space and time.'